Pulsed current-voltage characteristics of AlGaN/GaN high-electron-mobility-transistors on HR-Si substrate - Lee, Wei Yi. (2009)
In recent years, much research has been carried out on AlGaN/GaN high-electron-mobility transistors (HEMTs) on high resistivity (HR) silicon substrate. AlGaN/GaN HEMT is popular for its advantages for high-power and high-frequency applications. Though AlGaN/GaN HEMT showed high power performance [3], still the devices are suffering from drain current collapse [4]. To evaluate the current collapse, pulsed current-voltage measurement is an effective tool. In this project, the pulsed current-voltage characteristics of the device have been investigated. Devices of different gate-drain lengths, LGD were used. Literature reviews on HEMT’s device structure and characteristics were first carried out to have a clear understanding on the necessary theories and knowledge required. This made analysis on the results much easier later. Three types of measurements were performed – static (DC) IDS-VDS, pulsed IDS-VDS and transient current characteristics. The decrease of drain current with the increase of drain voltage is due to the effect of device self-heating.